A Weighted Discrete Universality Theorem for Periodic Zeta-Functions. II. Issue 6 (2nd November 2017) - Macaitienė, Renata; Stoncelis, Mindaugas; Šiaučiūnas, Darius
Abstract: In the paper, a weighted theorem on the approximation of a wide class of analytic functions by shifts ζ ( s + ik α h ; 𝔞), k ∈ ℕ, 0 < α < 1, and h > 0, of the periodic zeta-function ζ ( s ; 𝔞) with multiplicative periodic sequence 𝔞, is obtained.